Empowerment of Posyandu Cadres through Daily Emergency Training to increase Emergency Preparadeness - Mulyana, Budi; Pamungkas, Rian Adi; Rosya, Ernalinda; Rahman, Fauzan Habibi; Damanik, Vevi Sustria; Susanti, Ayu Retno; Gracia, Gracia (Universitas Padjadjaran, 2024)
Emergency conditions can happen to anyone, anywhere, and at any time. The success of helping victims depends on the accuracy and speed of each stage of the Integrated Emergency Management System. Therefore, Integrated Health Service Post, cadres must be equipped with first aid knowledge and skills as community facilitators in obtaining essential health services. This research, integrated with community service, aims to increase the understanding of Integrated Health Service Post cadres so they are ready to face daily emergencies. The method used is quantitative research of a pilot study with a pre-post one group quasi-experimental design. The intervention provided was training with a case study approach, lectures, and reflection on five skills to 10 people for two days. The skills provided are essential assistance, fainting assistance, fracture assistance, and rescue processes. The results of research integrated with community service showed that by forming a response team consisting of 10 people, partners' knowledge increased from an average of 46 to 71. Partners were also provided with skills videos and pocketbooks for long-term knowledge and skills. This research performance, which is integrated with community service, provides satisfaction to partners, where partners give an average score of 7.5 (0-10). This emergency training is effective in increasing readiness through increasing knowledge and skills.Keyswords: Emergency, integrated health service post, knowledge, readiness, training.